Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Timelapse microscopy of the misfolding protein guk1-7-GFP in recovery after heat stress in Hsp70- and Hsp104-mutant yeast strains - Hanzén, Sarah; Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Timelapse microscopy of yeast cells during recovery after 30 minutes of heat shock. The yeast was cultivated in complete synthetic media with 2 % glucose as carbon source. All strains produce the misfolding protein guk1-7-GFP.
The dataset was collected through timelapse microscopy of the same yeast cells for 2 hours.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Bildsekvens av jästceller under återhämtning från 30 minuters värmestress. Jästen har odlats i komplett syntetiskt media med 2 % glukos som kolkälla. Alla stammar producerar det felveckade markörproteinet guk1-7-GFP. Datasetet inhämtades genom fluorescensmikroskopi var 10:e minut av samma jästceller under 2 timmar.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Bildsekvenser över tid av den felveckande proteinmarkören guk1-7-GFP under återhämtning efter värmestress i Hsp70- och Hsp104-mutanta jäststammar
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi